Comparative Analysis of National Qualifications Frameworks in Higher Education of Ukraine and European Countries - Osadchyi, Viacheslav; Symonenko, Svitlana (Pedagogical Discourse, 2015)
The article deals with the problems of introduction of the National Qualifications Framework of Ukraine and its correlation with the European Qualifications Framework and national qualifications frameworks of European countries. National qualifications frameworks of some European countries in the field of higher education are analysed. The historical context, the structure, the content and the peculiarities of the European Qualifications Framework and the national qualifications frameworks of Ukraine, Germany, Poland and Denmark are considered. It was noted out that the national qualifications frameworks of European countries are based both on the Framework for Qualifications of the European Higher Education Area and the European Qualifications Framework for Lifelong Learning which are the metasystems aimed to improve qualifications transparency in Europe and to support lifelong learning and work mobility. The comparative analysis of descriptors of knowledge, skills, communication, autonomy and responsibility of the National Qualifications Framework of Ukraine and the national qualifications frameworks of Germany, Poland and Denmark in the field of higher education is carried out. Similarities and differences in descriptors of national qualifications frameworks in the field of higher education are highlighted. The similarity of knowledge descriptors in the field of higher education with knowledge improvement and progressive change of knowledge character is demonstrated. The absence of communication descriptors in the European Qualifications Framework is emphasized. It is pointed out that communication descriptors can be found in the national qualifications frameworks of Germany, Poland and Denmark as a part of other descriptors. The possibility of application of comparative analysis results in working out a development strategy of academic and professional mobility in higher education is discussed.